The mentally handicapped person with epilepsy: a comparative study investigating psychosocial functioning. - Espie, C; Pashley, A; Bonham, K; Sourindhrin, I; O'Donovan, M (1989)
A sample of institutionalized, mentally handicapped adults who suffered from epilepsy was compared with a matched control group without epilepsy in order to investigate profiles of adaptive skills and of behavioural disturbance. Results suggested that mentally handicapped people with epilepsy have consistently poorer life skills than their peers with no epilepsy but behavioural disturbance was not significantly elevated, except for a small sub-group whose epilepsy was resistant to pharmacological control. These results are discussed with reference to past research and management implications are considered.